The Epstein-Barr Virus Promoter Initiating B-Cell Transformation Is Activated by RFX Proteins and the B-Cell-Specific Activator Protein BSAP/Pax5 - Tierney, Rosemary (American Society for Microbiology, 2000)
Epstein-Barr virus (EBV)-induced B-cell growth transformation, a central feature of the virus' strategy for colonizing the human B-cell system, requires full virus latent gene expression and is initiated by transcription from the viral promoter Wp. Interestingly, when EBV accesses other cell types, this growth-transforming program is not activated. The present work focuses on a region of Wp which in reporter assays confers B-cell-specific activity. Bandshift studies indicate that this region contains three factor binding sites, termed sites B, C, and D, in addition to a previously characterized CREB site. Here we show that site C binds members of the ubiquitously expressed RFX family of proteins, notably RFX1, RFX3, and the associated factor MIBP1, whereas sites B and D both bind the B-cell-specific activator protein BSAP/Pax5. In reporter assays with mutant Wp constructs, the loss of factor binding to any one of these sites severely impaired promoter activity in B cells, while the wild-type promoter could be activated in non-B cells by ectopic BSAP expression. We suggest that Wp regulation by BSAP helps to ensure the B-cell specificity of EBV's growth-transforming function.